PECULIARITIES OF HEADACHES IN CHILDREN WITH RHEUMATIC ARTHRITIS - T.V. Podkletnova; E.I. Alexeeva; L.M. Kuzenkova; E.V. Uvakina ("Paediatrician" Publishers LLC, 2009)
Headache is the more often seen complaint in patient with rheumatoid arthritis (RA) at the visit to the neurologist. The objective of this study is analysis of headaches in children with different types of RA. 166 patients with different types of rheumatoid arthritis were examined, 65 (39,1%) children had complaints to the headaches. All patients with complaints to the headaches underwent complex examination - taking neurological history, neurological examination, and radiography of cervical part of spinal column in 2 projections, Doppler sonography of cervical vessels, eye grounds examination. Analysis of symptoms of headaches makes possible dividing it to the main types in patients with rheumatoid arthritis: craniocervicalgia, vascular headaches, and secondary headaches on the ground of RA exacerbation, intoxication, and steroid arterial hypertension, and stress headaches. It was shown, that headaches can be a result of both disease and its antirheumatic treatment. Key words: children, headaches, juvenile arthritis. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):27-34)